2020
DOI: 10.5114/pedm.2020.97466
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D level may be associated with body weight and body composition in male adolescents; a longitudinal study

Abstract: Introduction: The prevalence of both obesity and vitamin D deficiency has been dramatically increased worldwide. Aim of the study: This study aimed to investigate the association between vitamin D serum level and anthropometric indices of overweight and obese male adolescents at baseline and after 18 weeks of a weight reduction intervention. Methods: This study was carried out on 90 male students aged 12 to 16 years who were randomly selected from two schools in Tehran, Iran. The participants were assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Our study also found that body weight exclusively breastfed infants was positively associated with infant vitamin D su ciency. Existing studies mostly focused on vitamin D and obesity in non-children, and it is commonly recognized that serum vitamin D is lower in high body weight and obese people (30,31), but recent evidence from review a study indicated that the link between vitamin D and obesity remains controversial due to important limitations and confounding of studies (32). Current study on the infant body weight and serum vitamin D status are scare.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that body weight exclusively breastfed infants was positively associated with infant vitamin D su ciency. Existing studies mostly focused on vitamin D and obesity in non-children, and it is commonly recognized that serum vitamin D is lower in high body weight and obese people (30,31), but recent evidence from review a study indicated that the link between vitamin D and obesity remains controversial due to important limitations and confounding of studies (32). Current study on the infant body weight and serum vitamin D status are scare.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these differences may be the differences in doses of vitamin D supplementation and also differences in seum level of vitamin D. Doaei et al reported that the serum level of vitamin D is inversely associated with obesity. However, short term changes of serum vitamin D was not related to changes in weight ( Doaei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low levels of vitamin D were also associated with an increase in adiposity and a higher fat infiltration in the muscle tissue [ 27 ]. In fact, vitamin D levels were lower among adolescents with obesity when compared with non-obese individuals [ 28 ]. It is important to note that low vitamin D levels in children have been linked to obesity but not to other cardiovascular risk factors such as hyperglycemia [ 29 ].…”
Section: Dietary Management Of Diabetes and Bone Metabolism: Do They ...mentioning
confidence: 99%